Trapped-Mode Resonance Regime of Thin Microwave Electromagnetic Arrays with Two Concentric Rings in Unit Cell. (31st May 2011) - Kawakatsu, M. N.; Dmitriev, V. A.
Abstract : We present a theoretical study of reflection and transmission characteristics of a microwave planar array on a thin dielectric substrate with unit cell made of two concentric rings. This array possesses high quality factor transmission resonance with polarization insensitivity for normally incident plane wave. This resonance is defined by the trapped-mode regime. We show that for oblique incidence, there are some differences in characteristics of the array and a small change in quality factor of the trapped-mode resonance.